OH functionalization on carbon nanotube using (O2-H2) gas mixture DC glow discharge - Thandavan, T.M.K.; San Wong, C.; Gani, S.M.A.; Nor, Roslan Md (Springer Verlag, 2012)
The O H functionalization of carbon nanotube (CNT) was studied using oxygen-hydrogen (O2-H2) gas mixture direct current (DC) glow discharge plasma technique for cathode/CNT-anode separation of 0.10 Â± 0.01 cm. O2 and H2 were fixed at flowrate of 10.0 ml/min in order to obtain gas mixture ratio of 1:1. During the (O2-H2) gas mixture DC glow discharge, current-voltage ( I- V) characteristic of gaseous species studied for various settings of gas pressures 1, 2, 3 and 4 mbar. The voltage at gap between cathode/CNT and anode, a breakdown voltage, was identified as "functionalization voltage" ( V func). V func was noticed responsible for functionalization of functional groups on sidewall of CNT. The V func were recorded as 796, 707, 594, and 663 V for gas pressures of 1, 2, 3 and 4 mbar, respectively. The co-relation between V func and gas pressure was identified as linear relationship. But a voltage obtained due to the CNT/Cathode fall shows exponential relationship with the gas pressures. The possibility of O H functionalization was proved using Fourier transmission infra-red (FTIR) spectroscopy. Hydroxyl (-OH), carboxyl (-COOH), and carbonyl (-C=O) functional groups were identical as identified in the FTIR spectra. The field emission scanning electron microscope images show significant changes in the morphology of CNT which proves that the DC gas discharge plasma is a possible technique for O H functionalization on the sidewall of CNT.